Pro-inflammatory cytokines and insulin resistance in postmenopausal women with central obesity: A cross-sectional analytical study - Khalaf, M. S.; Hussein, W. N. (Regulatory Mechanisms in Biosystems, 2025)
The postmenopausal period is characterized by hormonal fluctuations that predispose women to increased visceral adipos i ty, chronic low-grade inflammation, and impaired glucose-insulin homeostasis. Pro-inflammatory cytokines, particularly TNF-α and IL-6, are believed to play integral roles in this interplay. This study aimed to investigate the association between circula t ing levels of TNF-α and IL-6 and insulin resistance (HOMA-IR) in postmenopausal women across different BMI categories, while accounting for relevant lifestyle and demographic factors. A total of 240 postmenopausal women aged 45–65 years were classified as normal weight, overweight, or obese. Anthropometric indices (BMI, WHR, WHtR), serum levels of TNF-α, IL-6, insulin, fasting glucose, and HbA1c were measured. Insulin resistance was calculated using the HOMA-IR formula. Lifestyle data were collected through structured questionnaires. Obese participants exhibited significantly higher levels of TNF-α (17.16 ± 3.22 ng/mL), IL-6 (9.03 ± 2.29 ng/mL), insulin, and HOMA-IR. TNF-α and IL-6 levels showed strong positive correlations with insulin resistance markers. Unhealthy lifestyle patterns, such as physical inactivity and increased meal frequency, were also more prevalent in the obese group. TNF-α and IL-6 appear to be early inflammatory biomarkers associated with metabolic dysregulation in postmenopausal women with central obesity. Screening for cytokine levels alongside HOMA-IR may enhance early identification of metabolic risk. Lifestyle modification should remain a cornerstone of preventive interventions in this population.